Pengaruh Aspek Rentabilitas Dan Likuiditas Terhadap Kesehatan Bank Umum Syariah Tahun 2017-2021 - Laili Istiqoma; Rafidah; Nurfitri Martaliah (Jurnal Publikasi Manajemen Informatika, 2023)
The purpose of this research was to determine the effect of Earning and Likuidity on the Health level of Sharia Commercia Bank for the 2017-2021. That is determine the effect of Return On Asset (ROA), Operational Cost of Operating Income (BOPO) and Financing to Deposit Ratio (FDR) on Capital Adequacy Ratio (CAR) at Sharia Commercial Bank for the 2017-2021. The research uses a quantitative approach. Sampling was based on purposive sampling, and tested with Classical Assumption Test, F test, T test, Panel Data Regression analysis. The result of the study explain that simultaneously the ROA, BOPO and FDR variables have a significant positive effect on the CAR variable. While partially the ROA variable effects significantly (negative) on the CAR, the BOPO variable effect significantly (negative) on the CAR and the FDR variable effect negative not significant on the CAR.